Penciptaan Ilustrasi Digital Buku Cerita Anak dengan Judul “Mencari Robung” untuk Balai Bahasa Sumatera Utara - Widya Arditta Siregar; Raden Burhan Surya Nat Diningrat (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
The creation of digital illustrations in children's storybooks plays a crucial role in supporting character education from an early age. This thesis aims to illustrate a children's storybook titled Mencari Robung, published by the Balai Bahasa Sumatera Utara. Mencari Robung is a bilingual story written in Indonesian and Melayu, carrying themes of nature and the environment, with the goal of introducing character values and cultural insights to children.The method used in this illustration creation is digital drawing in a cartoon style using Adobe Photoshop CC 2019. The creative process involves several stages, including literature study, script analysis, initial sketches, coloring, and finalizing the illustrations. The resulting illustrations are expected to effectively communicate the story’s content in a clear, engaging, and easily understandable manner for children. The outcome of this creation is a picture book with high-quality illustrations at a resolution of 300 dpi, which not only enhances the visual appeal but also serves as an effective educational medium. Furthermore, this research is expected to serve as a reference for artists, writers, and academics in developing children's book illustrations that support literacy and character education.